Simulation of Future Land Use for Water Management - Assessing the suitability of scenario-based modelling - Jasper Dekkers; Eric Koomen (European Regional Science Association (ERSA), 2005)
The problem of water shortage is increasingly getting attention within the field of water management, even in the wet Netherlands. Clean ground and surface water may become too scarce to allow for sustainable use for various functions. In order to assess the magnitude of this problem a water shortage study has been started in the Netherlands, in which the impact of land use change is an important issue. Land use models can help translate hypotheses regarding future spatial developments into maps of a possible future. These scenarios can then be used in spatial planning processes. Future land use is greatly influenced by current land use, autonomous socio-economic developments, current policy and in the long term climate changes and other changes in the physical environment. By developing scenarios that are clearly different from each other, especially on the factors that influence the problem of water shortage, divergent images of the future have been generated for 2030. In this way, a first impression has been developed for the bandwidth in which future developments can occur. The goal of this paper is to evaluate whether we are able to generate new, spatially diverse scenario's based on existing material within a very short time period.
Keywords: 330